2019
DOI: 10.1155/2019/8149897
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Associated Risk Factors of Rift Valley Fever in Domestic Small Ruminants in the North Region of Cameroon

Abstract: Rift Valley fever (RVF) is a zoonotic vector borne infectious disease of major medical and veterinary importance particularly in sub-Saharan Africa. However, there is dearth of epidemiological knowledge of the disease in Cameroon. We conducted a cross-sectional study (January 2016–January 2017) to investigate the seroprevalence and potential risk factors of Rift Valley fever virus (RVFV) in sheep and goats in the North region of Cameroon. Stratified sampling approach was used to select herds where sera were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 35 publications
3
14
1
Order By: Relevance
“…Poueme et al [ 23 ] reported the presence of RVFV-specific antibodies in Cameroonian livestock and higher seroprevalence rates in Pitoa and Lagdo due to the present risk factors in these areas. The previous study of Rissmann et al [ 24 ] also confirmed the circulation of RVFV in Cameroon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poueme et al [ 23 ] reported the presence of RVFV-specific antibodies in Cameroonian livestock and higher seroprevalence rates in Pitoa and Lagdo due to the present risk factors in these areas. The previous study of Rissmann et al [ 24 ] also confirmed the circulation of RVFV in Cameroon.…”
Section: Discussionmentioning
confidence: 99%
“…Despite reports of RVFV-specific antibodies in livestock from the North Region of Cameroon [ 23 , 24 ], no entomological study on the potential vectors that play an important role in the transmission and spread of the virus [ 5 , 25 ] has been carried out before. In-depth knowledge of the bioecological parameters of vectors is essential to delineate risk areas and predict outbreaks.…”
Section: Introductionmentioning
confidence: 99%
“…aegypti Humans, animal (migrant birds, francolin, calao, rapace, Passeriformes, pigeons, mammals) Garoua, Maroua, Ngaoundere, Buea, Bertoua, Yaoundé, Douala [ 96 ] Rift Valley fever Rift Valley fever virus Aedes spp., Culex spp. Humans, goats, sheep, cattle, gazelles, buffalo Countrywide (in all regions of the country) [ 19 , 21 , 30 , 92 ] Other viruses Tiko virus , Kumba virus , Semlinki virus , Okola virus , Tahina virus , Onyong nyong virus , Ilesha virus , MIDV , NTAV , WESV , B unyamwera virus , Eret virus , Silbu virus , Tatanguine virus , Osuntu virus , Uganda virus , Sindbis virus , Nkolbisson virus , SPOV Culex spp., Mansonia spp., Coquillettidia spp., Eretmapodites spp. Humans, animals (mammals, birds) Kumba, Obout, Buea, Ebogo, Ototomo, Mbalmayo, Akonolinga, Nkolbisson, Okola, Ofoumselek, Yaoundé [ 28 , 84 , 86 – 90 ] …”
Section: Mosquito-borne Diseases and Pathogens Circulating In Cameroonmentioning
confidence: 99%
“…The most prevalent include dengue, chikungunya, yellow fever, zika, and Rift Valley fever viruses [ 19 , 21 , 30 , 83 91 ]. To date, at least 26 different arbovirus diseases belonging to five families have been reported in Cameroon (see Table 1 ) [ 8 , 21 , 30 , 31 , 81 , 84 , 92 , 93 ]. Among them, 18 arboviruses have been detected in humans [ 86 , 87 , 94 , 95 ], and 14 are transmitted by mosquitoes ( Aedes , Culex , Eretmapodites , Mansonia , and Anopheles ) (Fig.…”
Section: Mosquito-borne Diseases and Pathogens Circulating In Cameroonmentioning
confidence: 99%
See 1 more Smart Citation